RARE-33. GIANT CELL TUMOR OF THE SKULL BASE WITH A HISTORY OF A SUCCESSFUL RESPONSE TO DENOSUMAB AND LATER DEVELOPING A SECOND TUMOR. (4th December 2020) - Avagyan, Manushak; Tamamyan, Gevorg; Danielyan, Samvel; Harutyunyan, Martin; Karapetyan, Nune; Karamyan, Nerses; Vardevanyan, Hovhannes; Mkhitaryan, Armen; Bardakhchyan, Samvel
Abstract: BACKGROUND: Giant cell tumor of bone(GCTB) is a rare neoplasm with unpredictable behavior, possible malignant transformations, and/or lung metastases. Surgery is usually the treatment of choice. In unresectable or metastatic cases, treatment with denosumab is a new treatment option. CASE PRESENTATION: A 14-years-old female presented with cachexia, dysphagia, diplopia, discoordination, strabismus, and multiple cranial nerve palsies in 10.2015. MRI revealed intra-extracranial mass arising from C2 vertebrae, compressing the medulla oblongata and the left cerebellar hemisphere, invading to the sphenoid bone and nasopharynges. Biopsy showed a GCTB. Surgical resection was done, which was incomplete because of tumor location (cranial nerve and vertebral artery involvement). Then local radiation therapy was performed 50.4Gy. During RT patient's condition declined and MRI showed disease progression. Treatment with denosumab 120mg q4w was initiated in 03.2016, which yielded successful results. Disease was under control for three years until 03.2019. Then she returned with clinical symptoms of diplopia and severe headache. MRI showed local tumor progression. Repeated biopsy revealed undifferentiated pleomorphic sarcoma, which could be either a malignant transformation of GCTB or a new tumor. The patient later underwent two cycles of chemotherapy with Ifosfamide/Doxorubicin. MRI after 2nd cycle showed marked tumor progression. The patient didn't receive any further treatment because of cachexia and died due to disease progression in 12.2019. CONCLUSION: To our knowledge, this is the youngest patient ever reported with a skull base tumor with such a clinical development, successful and long-time remission with denosumab and with such a chemotherapy-resistant malignant transformation or second cancer.